Sociology of Wisdom: The Present and Perspectives - Jijyan, Anahit; Kocharyan, Romik; Qocharyan, Nerses (Տիգրան Մեծ)
The article presents a new concept of sociology and social knowledge, according to which the calling and truth of social knowledge are to become and improve as a thought that understands and interprets the truth of human interaction and interimpaction. Therefore, social science and, in particular, sociology is rethought and improved as a “sociology of wisdom”.
Keywords: Social philosophy